Aerobic Exercise Effects on Ocular Dominance Plasticity with a Phase Combination Task in Human Adults - Zhou, Jiawei (Neural plasticity, 2017)
Several studies have shown that short-term monocular patching can induce ocular dominance plasticity in normal adults, in which the patched eye becomes stronger in binocular viewing. There is a recent study showing that exercise enhances this plasticity effect when assessed with binocular rivalry. We address one question, is this enhancement from exercise a general effect such that it is seen for measures of binocular processing other than that revealed using binocular rivalry? Using a binocular phase combination task in which we directly measure each eye's contribution to the binocularly fused percept, we show no additional effect of exercise after short-term monocular occlusion and argue that the enhancement of ocular dominance plasticity from exercise could not be demonstrated with our approach